Estetika Permainan Musik Barat pada Big Band Salamander - Dirgualam, Oki; Suganda, Dadang; Wibawa, Buky; Sufianto, Kunto (Paradigma: Jurnal Kajian Budaya, 2021)
This article describes the aesthetics of the big band jazz music by Salamander Big Band. Aesthetics is a study of the processes that occur in three basic elements: aesthetic objects, aesthetic subjects, and aesthetic values related to aesthetic experiences, aesthetic properties, and attractive and unattractive parameters. This paper presents the basic elements of western music aesthetics, especially big band jazz music, and how Salamander Big band can implement the aesthetic values of western jazz big band music in the music played. This research uses a qualitative approach with a descriptive analysis method. Through a process of appreciation, habituation, additional insight into jazz music and continuous and consistent practice, Salamander Big Band members can adapt to cultures from outside Indonesia's popular music culture, namely playing American big band music with the right aesthetic.